Electrocardiographic parameters in single and twin pregnant and non-pregnant sheep - Balikci, Engin; Yildiz, Atilla (Indian Veterinary Journal, 2006)
This study is aimed at detection ECG changes between pregnant and nonpregnant sheep, and those having single and twin pregnancy.